Stress i nekotorye problemy adaptacionnych perestroek pri sportivnych nagruzkach - Rozenfeld, A. S.; Maevski, E. I. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The stress can result in the derangements of the balance of physiological systems and the constancy of internal environment. It is necessary to support the constancy of physical and chemical parameters of an organism for the counteraction of the destructive influences of stress. The experiments executed at the level of the complete organism and tissue for the first time HAD showed the opportunity of maintenance of the acid-base balance at loads due to increase of the contribution of mitochondrions in synthesis of adenosinetriphosphate by use of exogenous mitochondrion substrata. The oxidation of exogenous succinate in an organism up to ??2 repeatedly grows at loads. The range of reactance of the acid-base balance of blood is increased as well as at growth of sports skill after intake of succinate: the acidosis decreases at standard on capacity physical loads and grows the ability to withstand the deep acidosis at maximum loads. The exogenous succinate in an organism renders direct substratum and mediated influence, including hormonal system.